2011
DOI: 10.1128/aem.02300-10
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Antimicrobial Feed Additives on Broiler Commensal Posthatch Gut Microbiota Development and Performance

Abstract: The effects of avilamycin, zinc bacitracin, and flavophospholipol on broiler gut microbial community colonization and bird performance in the first 17 days posthatch were investigated. Significant differences in gut microbiota associated with gut section, dietary treatment, and age were identified by terminal restriction fragment length polymorphism (T-RFLP), although no performance-related differences between dietary treatments were detected. Similar age-related shifts in the gut microbiota were identified re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
112
3
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(132 citation statements)
references
References 62 publications
13
112
3
4
Order By: Relevance
“…In a pioneering work, by using T-RFLP analysis together with multivariate statistical methods, Torok et al (2011a) identified and characterized changes in gut microbiota development in chickens in response to enzyme or antimicrobial agents in feed that had performance implications. More specifically, an overgrowth of some microorganisms including enterobacteria in the intestine has been reported (Bourlinoux et al, 2003;Pelicano et al, 2005) to result in mucosal impairment, villus erosion and damage to the intestinal cells, thus reducing its nutrients' absorptive potential.…”
Section: Discussionmentioning
confidence: 99%
“…In a pioneering work, by using T-RFLP analysis together with multivariate statistical methods, Torok et al (2011a) identified and characterized changes in gut microbiota development in chickens in response to enzyme or antimicrobial agents in feed that had performance implications. More specifically, an overgrowth of some microorganisms including enterobacteria in the intestine has been reported (Bourlinoux et al, 2003;Pelicano et al, 2005) to result in mucosal impairment, villus erosion and damage to the intestinal cells, thus reducing its nutrients' absorptive potential.…”
Section: Discussionmentioning
confidence: 99%
“…Age-dependent colonisation by E. faecalis and E. cecorum was confirmed in this study. The composition of the commensal flora of the poultry intestine may change under the influence of diet, age, stress, type of litter, and especially antibiotic use (Burkholder et al, 2008;Torok et al, 2009Torok et al, , 2011. According to the literature, E. cecorum infection appears to be most common in broiler flocks at the age of 3-6 weeks, and in broiler breeders aged 3.5-18 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity of qPCR assays was tested against dilutions of known amounts of target (plasmid standards). Sequences of 16S rRNA representative of L. crispatus G. anatis (JF798066), E. coli (JF798201) and eubacteria (JF798192) were cloned into pGEM-T (Promega, Madison, WI, USA), as previously described (Torok et al 2011a(Torok et al , 2011b. Plasmids were quantified using spectrophotometry (NanoDrop 2000, Thermo Scientific, Wilmington, DE, USA).…”
Section: Nucleic Acid Extractionmentioning
confidence: 99%
“…Specificity of qPCR assays was confirmed visually using gel electrophoresis, as well as by determining the nucleotide sequence of resulting PCR amplicons. Purified PCR amplicons were cloned and recombinant plasmid recovered and sequenced, as previously described (Torok et al 2011a). All qPCR amplicons were generated from total nucleic acid extract obtained from chicken gut digesta and associated gut tissue that was representative of a diverse bacterial template.…”
Section: Nucleic Acid Extractionmentioning
confidence: 99%